(untitled) (Bangladesh Journal of Animal Science, 2023)
Feed substrate containing probiotic culture of Lactobacillus acidophilus, Bacillus subtilis and Sacharomyces cerevicae were prepared for feeding calves. Twelve 2 weeks old calves were distributed equally in two groups (6 calves in each) and supplemented with (treated) or without probiotic feed (Control). Calves were reared in an individual pan and provided with ad libitum suckling, calf starter, and soft green grass. In 90 days trial period data were collected on growth performance, blood metabolic profile, immune status, fecal microbial load, morbidity etc. It was observed that milk intake, dry matter intake (DMI), daily gain and feed conversion ratio (FCR) were not differed (P>0.05) between treatments. Claves under the probiotic fed group voided feces of better physical properties (color, odor and consistency) compared to the control. Weekly E. coli count (log10CFU/g) in feces was found lower (P<0.01) in the probiotic group compared to the control. The plasma IgG (ng/ml) concentration was found higher (P<0.05) in probiotic group than in the control, and total cholesterol level tended to be high (P=0.071) in the same group. It is concluded that, probiotic feed improved fecal characteristics, lesser E. coli load in feces, lowered diarrheal incidence and improved immunoglobulin status of calves from 15th to 105th days of age. Bangladesh Journal of Animal Science, 52 (2): 45-54